Observation of disorder-induced boundary localization - Bing-Bing Wang; Zheyu Cheng; Hong-Yu Zou; Yong Ge; Ke-Qi Zhao; Qiao-Rui Si; Shou-Qi Yuan; Hong-Xiang Sun; Haoran Xue; Baile Zhang (Proceedings of the National Academy of Sciences, 2025)
Bloch wavefunctions in crystals experience localization within the bulk when disorder is introduced, a phenomenon commonly known as Anderson localization. This effect is considered universal, being applicable to all types of waves, quantum or classical. However, the interaction between disorder and topology—a concept that has profoundly transformed many branches of physics—necessitates revisiting the original Anderson localization picture. For instance, in the recently discovered topological Anderson insulator, the introduction of disorder induces topological boundary states that can resist localization due to protection from line-gap topology. While line-gap topology applies to both Hermitian and non-Hermitian systems, non-Hermitian systems uniquely exhibit point-gap topology, which has no Hermitian counterparts and leads to the non-Hermitian skin effect. Here, we experimentally demonstrate disorder-induced point-gap topology in a non-Hermitian acoustic crystal. This crystal, with non-Hermitian disorder in nearest-neighbor couplings, exhibits the non-Hermitian skin effect, where all eigenstates localize at a boundary. Interestingly, the boundary where localization occurs—either the left or right—depends on the strength of the disorder. As the disorder strength increases, the direction of boundary localization can be reversed. Additionally, we observe a “bipolar” skin effect, where boundary localization occurs at both the left and right boundaries when disorder is introduced in next-nearest-neighbor couplings. These findings experimentally reveal a non-Hermitian mechanism of disorder-induced localization that goes beyond the conventional framework of Anderson localization.